The Review of Hong Jing Tian in an Academic Database CNKI - ชำนาญกิจ สุพิชดา; พันงา คุณส่ง เยส วรรณกานต์; Keawsuwan , Chatuwit (Thai Journal of East Asian Studies, 2022)
This article is the result of the researcher team uses Chinese language knowledge and Traditional Chinese medicine study to systematize the benefits of Hong Jing Tian (Rhodiola rosea, 红景天) by researching 12 articles in total which presented in an academic database called China Knowledge Resource Integrated (CNKI). And found that Hong Jing Tian has antioxidant, antiviral, anticancer, antihypertensive, antihypertensive properties. It also nourishes various organs including heart, liver, kidneys, lungs, blood system and can also help reduce fatigue, help with memory and enhance immunity. From what we have studied, the researchers think that there should be further studies on the medicinal properties of Hong Jing Tian in Thailand. As an alternative choice to those who are interested in using this herb to heal or nourishes the body. It is likely that additional properties other than what is currently available may be found.